Effect of Far-Red Light and Nutrient Solution Formulas on Calendula Production in a Plant Factory - Maitree Munyanont; Na Lu; Thanit Ruangsangaram; Michiko Takagaki (Biology)
Calendula (Calendula officinalis L.), an edible and medicinal flower, faces challenges in yield uniformity and quality stability under open-field cultivation. Plant factories with artificial lighting (PFALs) are highly controlled systems that enable year-round production, efficient resource use, and consistent crop quality, making them promising for the cultivation for calendula. To optimize calendula cultivation in PFALs, this study investigates the effects of far-red (FR) light and nutrient solution modification on calendula growth, flowering, and nutrient use efficiency (NUE). The experiment was conducted using a dwarf calendula cultivar, ‘Orange Gem’. After transplanting, seedlings were subjected to a 2 × 3 factorial design comprising white (W) and end-of-day far-red (EOD-FR) lighting, in combination with three ammonium (NH4+) levels (1/3×, 1×, and 3× of the Enshi formula). The EOD-FR lighting and the increase in the NH4+ level resulted in taller plants and earlier first flower appearance. The shoot fresh and dry weight, the number of flowers, and the flower yield also increased under the higher NH4+ concentration, regardless of the light treatment. The 3× NH4+ treatment tended to enhance the nutrient absorption, leading to the highest nutrient use efficiency (NUE) based on the flower yield. These findings suggest that the application of EOD-FR lighting and high NH4+ in nutrient solution can improve calendula productivity and resource-use efficiency in PFALs.